Multiresponse Optimization of Mechanical and Physical Adsorption Properties of Activated Natural Fibers Hybrid Composites - G. Velmurugan; V. Siva Shankar; L. Natrayan; S. Sekar; Pravin P. Patil; M. Senthil Kumar; Subash Thanappan (Adsorption Science & Technology)
In the current scenario, natural fiber-based biodegradable composites have increased because natural composite fibers are very cheap, biodegradable, lightweight, fireproof, and nontoxic. The present research work was carried out to optimize the mechanical properties of hybrid composites reinforced by Calotropis gigantea and hemp. To achieve these objectives, the following process parameters were determined, and RSM carried out optimization with the Box-Behnken experimental setup at three different levels: compression molding temperature (°C), pressure (bar), and time (min). The fibers were pretreated for 4 hours with a 5% NaOH solution to prevent moisture absorption. Regression equations were constructed to evaluate the mechanical properties, and the best process parameters were established. The results reveal that a pressure of 35 bar, a time duration of 7 minutes, and a temperature of 176°C are the best conditions for compression molding. The second aim was to compare CGF and hemp fiber-derived activated carbon adsorbents by determining physical adsorption properties, chemical compositions, and scanning electron microscope. Natural fibers were shown to be ideal candidates for manufacturing mesoporous activated carbon adsorbents with high surface area (1389–1433 m2/g), high mesopore percentage (63–68%), and high carbon content (80–87%). Even though hemp activated carbon had a greater mesoporous structure (69%) than CGF-derived activated carbons, the CGF-derived activated carbons had larger surface areas and higher C content.